2019
DOI: 10.35940/ijitee.i1128.0789s219
|View full text |Cite
|
Sign up to set email alerts
|

Control of CD Nozzle Flow using Microjets at Mach 2.1

Abstract: This paper reports the outcome of the wind tunnel investigation performed to study the effectiveness of the control jets to regulate the base pressure in an abruptly expanded circular pipe. Tiny jets four in a number, of 1 mm orifice diameter located at ninety degrees in cross shape along a pitch circle diameter (PCD) of 1.3 as a control mechanism were employed. The Mach numbers and the area ratio of the study were 2.1, and 4.84. The length-to-diameter (L/D) ratio of the duct tested was varied from 10 to 1. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Internal flow experiments have several advantages over exterior flow experiments: they use less air, eliminate support devices, and allow for easy measurement of the base pressure in the base region [5,6]. The primary benefit of an internal flow apparatus is that it enables absolute static pressure and surface temperature measurements not only during the expansion's entrance section but also in the wake zone [7,8]. Suddenly expanded flow is characterized by separation, recirculation, and reattachment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internal flow experiments have several advantages over exterior flow experiments: they use less air, eliminate support devices, and allow for easy measurement of the base pressure in the base region [5,6]. The primary benefit of an internal flow apparatus is that it enables absolute static pressure and surface temperature measurements not only during the expansion's entrance section but also in the wake zone [7,8]. Suddenly expanded flow is characterized by separation, recirculation, and reattachment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, recent findings have also shown that several studies are conducted with equivalent or variable Mach number and area ratios with the same NPR and L/D ratios. The majority of wall pressure flows were considered with varying the area ratio, such as 2.56 [ [103][104][105]110], and varying the Mach number for the same area ratio 2.56 with Mach 2 and 3 [106], 1.3. 1.9, and 2.4 [111] and for the area ratio 6.25 with Mach 1.1 and 1.5 [112] and 2.1 and 2.8 [113].…”
Section: Experimental Investigationmentioning
confidence: 99%
“…Muhammed et al, [14] focussed on the flow field around a non-circular cylinder and conclude that the pressure drag coefficient is in the range of 1 to 1.42. The convergent-divergent nozzle was studied for different area ratios by Khan et al, and Akhtar et al, [15][16][17][18]. It was found that the area ratio plays a vital role in base pressure distribution.…”
Section: Literature Overviewmentioning
confidence: 99%